A Poster Assignment Connects Information Literacy and Writing Skills. - Natalie Waters (Issues in Science and Technology Librarianship, 2015)
This paper describes the implementation of a poster assignment in a writing and information literacy course required for undergraduate Life Sciences and Environmental Biology majors with the Faculty of Agricultural and Environmental Sciences at McGill University. The assignment was introduced in response to weaknesses identified through course evaluations. Students were not making the connection between what was being taught by the librarian, the information literacy portion, and the course lecturer, the grammar and writing portion, because most lectures and all assignments were handled separately. Students also had trouble tying the relevance of this this required course to their other science courses. A poster assignment holds many advantages, one of which is a clear connection in course content between the two sections, as well as being a common communication method in the sciences. [ABSTRACT FROM AUTHOR]